2019
DOI: 10.1093/aje/kwy276
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Antimicrobial Resistance Surveillance: A Role for Lot Quality Assurance Sampling

Abstract: Global surveillance of antimicrobial resistance (AMR) is a key component of the 68th World Health Assembly Global Action Plan on AMR. Laboratory-based surveillance is inherently biased and lacks local relevance due to aggregation of data. We assessed the feasibility, sensitivity, and affordability of a population-based AMR survey using lot quality assurance sampling (LQAS), which classifies a population as having a high or low prevalence of AMR based on a priori defined criteria. Three studies were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…These limitations propagate into our prevalence estimates, and they should thus be interpreted as an approximation of the true prevalence in a country. Future unbiased surveillance will likely require novel approaches, e.g., population-based surveillance ( 33 , 34 ), for which the necessary resources and infrastructure are not yet in place. Our predictive framework provides a means to support the prioritization of investments required for this.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations propagate into our prevalence estimates, and they should thus be interpreted as an approximation of the true prevalence in a country. Future unbiased surveillance will likely require novel approaches, e.g., population-based surveillance ( 33 , 34 ), for which the necessary resources and infrastructure are not yet in place. Our predictive framework provides a means to support the prioritization of investments required for this.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of assessment of a prevalence estimate with corresponding confidence intervals, a LQAS-based surveillance approach classifies the prevalence to be above a pre-defined threshold determined on the basis of clinical criteria and guidelines [15]. The study showed that LQAS-based surveillance of the prevalence of AMR provided the opportunity to obtain locally relevant estimation in a timely and affordable manner that can be repeated for monitoring purposes [16]. Other surveillance approaches that provide unbiased population-based AMR prevalence estimates may provide similar solutions and need to be explored.…”
Section: Plos Onementioning
confidence: 99%
“…This also holds for Indonesia where information on AMR is infrequently derived from a limited number of university laboratories [13]. We know from our earlier work that AMR prevalence is high in Indonesia, and can differ markedly between settings and even hospital wards [14,15].…”
Section: Discussionmentioning
confidence: 92%
“…There is a clear need for strategies that can provide rapid and locally relevant information on AMR to guide empirical antibiotic treatment choices in a variety of settings. We showed earlier that this is possible by assessing whether the prevalence of AMR is above a clinically relevant level that precludes the use of an antibiotic, rather than attempting to assess a precise AMR prevalence [15].…”
Section: Discussionmentioning
confidence: 99%